1997
DOI: 10.1159/000201479
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Lymphocyte Proliferation in Human Acute Pancreatitis

Abstract: Purpose: We evaluated the proliferative response of lymphocytes to phytohemagglutinin P (PHA P), concanavalin A (Con A), and pokeweed mitogen (PWM) during the course of acute pancreatitis. Patients and Methods: Sixty consecutive patients with acute pancreatitis were studied within 48 h of the onset of pain, and 16 of them were also studied 1 month after complete recovery. According to the Atlanta criteria, 21 patients had severe disease and 39 had mild disease. Fifteen healthy subjects and 11 patients with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 6 publications
1
14
0
2
Order By: Relevance
“…0.01). Our findings are in agreement with other studies indicating that patients with severe AP often lack cutaneous responses to recall antigens supplied by the multitest CMI device within 72 h of admission [18], have depressed lymphocyte proliferative responses to mitogen stimulation within 48 h of onset of pain [19], and have high serum levels of both anti-and proinflammatory cytokines on presentation [20,21]. We also observed a significant inverse correlation between the percentage of HLA-DR+ and AP severity as assessed by MODS score and APACHE-II scores.…”
Section: Discussionsupporting
confidence: 93%
“…0.01). Our findings are in agreement with other studies indicating that patients with severe AP often lack cutaneous responses to recall antigens supplied by the multitest CMI device within 72 h of admission [18], have depressed lymphocyte proliferative responses to mitogen stimulation within 48 h of onset of pain [19], and have high serum levels of both anti-and proinflammatory cytokines on presentation [20,21]. We also observed a significant inverse correlation between the percentage of HLA-DR+ and AP severity as assessed by MODS score and APACHE-II scores.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the lymphocytic immune response occurs later and its main function is to mediate and resolve the preceding nonspecific inflammatory process. Prior studies have shown an association between lower peripheral lymphocyte counts and the severity of cases of acute pancreatitis [31,32,33]. Such decline in lymphocyte count in acute pancreatitis was attributed to apoptosis and was also associated with lymphocyte dysfunction [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Since no specific antigen is known, we used nonspecific mitogens to stimulate the PBMC. In patients with acute pancreatitis or patients with Crohn’s disease impaired lymphocyte proliferation after stimulation with lectins has been reported [18, 27]. Comparing all CP patients with controls, we did not find a significant difference (fig.…”
Section: Discussionmentioning
confidence: 51%